Investigating and Prosecuting International Crimes Committed in the Context of the Russian Aggression Against Ukraine: The Polish Involvement - Topa, Ilona (Acta Universitatis Lodziensis. Folia Iuridica, 2024)
The paper aims to present the available options relating to the investigation and prosecution of international crimes allegedly committed in Ukraine by the Russian authorities and members of the Russian armed forces. Firstly, it presents domestic Ukrainian criminal proceedings on these crimes. Then, the ongoing investigation in the International Criminal Court on war crimes and crimes against humanity as well as the initiatives to create a special international court that would deal with the responsibility for the crime of aggression are explored. Finally, considering substantial Polish involvement, it would be interesting to have an insight into how Poland already has and could, in the future, further contribute to bringing to justice the perpetrators of international crimes committed in Ukraine.